(untitled) (Revista de Ciências Agroveterinárias, 2004)
The liming can affect the development of the system root of the carambola with implications in the absorption of nutritious. It was aimed at to evaluate the effects of the limestone application in the chemical properties of the soil, in the nutrition of the plant and in the development of the system root of the carambola, cultivated in a Latosol Red acid distrofic. For this, limestone doses were analyzed, zero (control); 3.705 and 7.410 t ha-1, in soil samples collected, in the planting line, to 75 cm of the trunk, in layers of 0-20 and 20-40 cm of depth. The limestone was applied in at planting, incorporate (0-30 cm of depth). During 2o and 3o year of culture of the carambola, the effect of the liming in the soil and the nutrition of the fruit had been accompanied by. In 3o year of culture of the carambola, beyond the chemical analysis of the soil and leves (Ca), it was evaluated dry substance and text of Ca of the root of the fruit. The determination of the concentration of Ca in the soil is an indicative for the diagnosis of the growth potential to radical in carambola in formation phase.